2018
DOI: 10.4103/ijdr.ijdr_729_16
|View full text |Cite
|
Sign up to set email alerts
|

Various bio-mechanical factors affecting heat generation during osteotomy preparation: A systematic review

Abstract: Literatures of this review study have indicated that there are various bio-mechanical reasons, which affect the temperature rise during osteotomy and suggest that the amount of heat generation is a multifactorial in nature and it should be minimized for better primary healing of the implant site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Aghvami and collaborators considered the medullary cavity as a region of thermal dissipation, not showing a www.nature.com/scientificreports/ significant increase in temperature during drilling 31 . In addition, several authors described that bone density is much more important in raising the temperature than the depth of osteotomy 11,20,21 . Therefore, in this study, the thermocouples were inserted in a position with a depth of 3 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aghvami and collaborators considered the medullary cavity as a region of thermal dissipation, not showing a www.nature.com/scientificreports/ significant increase in temperature during drilling 31 . In addition, several authors described that bone density is much more important in raising the temperature than the depth of osteotomy 11,20,21 . Therefore, in this study, the thermocouples were inserted in a position with a depth of 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…3 Others evaluate the types of continuous or intermittent movements performed during the osteotomy 5,8,12 . And others focus on the various irrigation techniques: internal, external, single or double 2,4,8,[10][11][12][13] . Finally, one of the factors that have been studied the most is the one related to the geometry of the drill 6 .…”
mentioning
confidence: 99%
“…Nevertheless, it is the authors opinion that pilot‐drill protocol with free‐hand placement of the implants could be a viable option in case of simultaneous guided bone regeneration. As demonstrated by several studies, pilot‐drill implant placement showed inferior accuracy than fully‐guided implant placement 19‐23 . However, in case of simultaneous implant placement and guided bone regeneration, the pilot‐drill guide protocol, that controlled the pilot drilling only, could be recommend 14‐16 .…”
Section: Discussionmentioning
confidence: 99%
“…Chauchan et al confirmed that the wear of the dental implant drills influences their cutting capacity and therefore the working time and the heat transmitted to the peri-implant tissues during osteotomy site preparation [13]. In addition, Tehemar described the factors affecting heat generation during implant site preparation and highlighted the importance of sterilization techniques, density of the bone sites, and surface treatment of the dental implant drills in keeping the integrity of dental implant drills [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that heat transferred to bone tissue may cause hyperemia, necrosis, and fibrosis or even increase osteoclast activity [11,12]. Eriksson and Albrektsson reported that a temperature threshold about 47 • C might cause irreversible damage to bone tissues and hence osseointegration failure when osteotomy is maintained for one minute [13][14][15]. Scarano et al reported that repeated use causes drills to wear and reduces their efficiency, and the temperature increases each time a drill is used [16].…”
Section: Introductionmentioning
confidence: 99%